How the Big 4 got big: Audit culture and the metamorphosis of international accountancy firms. (September 2018) - Shore, Cris; Wright, Susan
New calculative techniques of management and accountancy are having a transformative effect on organisations, individuals and society. These processes are often associated with contemporary neoliberal capitalism, but what exactly is driving the proliferation of these measurement systems and how is this change actually occurring? We address these questions by exploring the history of the Big 4 international accountancy firms and their role in spreading audit culture and the rationalities of financial accountancy. Since the 1990s, the expansion of their remit from traditional auditing to a growing emphasis on consultancy services has increasingly blurred the boundary between their public watchdog role and their commercial interests. Combined with the changing values, career trajectories and 'habitus' of audit company professionals, and the weaknesses of self-regulation, this has resulted in problems for ethics and corporate social responsibility. Using ethnographic examples, we examine the metamorphosis that occurs as accountants, originally trained in the disciplines of financial probity, become more entrepreneurially oriented when they ascend to senior positions as company managers and partners. If the calculative practices of accountancy are central to modern forms of audit, we argue they are also transforming accountancy firms themselves into evermore calculative and financialised entities. We conclude by showing how the post-1990s shift from auditing to advisory services leads these companies to tread an ever-finer line between entrepreneurship and fraud.